Amygdalohippocampal neuroplastic changes following neuroleptic treatment with quetiapine in first-episode schizophrenia. (15th January 2014) - Poeppl, Timm B.; Frank, Elmar; Schecklmann, Martin; Kreuzer, Peter M.; Prasser, S. Julia; Rupprecht, Rainer; Hajak, Göran; Langguth, Berthold; Landgrebe, Michael
Abstract: Schizophrenia is a severe, debilitating, chronic disease that is accompanied by morphologic changes within the brain. However, it is unclear to what extent alterations of grey and white matter in schizophrenia are linked to the disease itself, or whether they are a consequence of neuroleptic treatment. Typical and atypical antipsychotics exert differential effects on brain structure. Moreover, atypical antipsychotics may have distinct profiles with respect to grey matter in schizophrenic patients. Findings on drug-induced grey matter changes are heterogeneous due to variation in stage of illness, duration of treatment and use of multiple antipsychotics. Using voxel-based morphometry applied to high-resolution magnetic resonance images, we show that monotherapy with the atypical agent quetiapine (mean daily dose = 445 mg ± 200 s.d. ) may induce structural brain changes in first-episode schizophrenia patients ( N = 20) within 21 d of treatment. Specifically, we demonstrate longitudinal macroscopic changes (i.e. grey matter increases) in the left amygdalohippocampal region that were predicted by drug plasma levels but not daily doses. These structural alterations were accompanied by a clinical improvement of schizophrenic symptoms. Comparison with healthy controls ( n = 30) showed that grey matter amount in the respective amygdalar region was significantly reduced in unmedicated first-episode schizophrenia patients. These findings suggest that drug-induced neuroplastic changes in schizophrenia can occur quickly and are dependent on pharmacokinetics.